Pahlawan dan penghianat dalam sejarah: Analisis peran individu dalam peristiwa sejarah - Sumardin, Oschar; Kabubu, Rusmala Dewi (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
Historical events inevitably involve the involvement of many figures who play a role in supporting or opposing the occurrence of an important event. In this study, the analysis aims to reveal the role of individuals in historical events, namely regarding the role of heroes and traitors. This research method uses a descriptive qualitative approach with secondary data collection techniques through literature reviews. Data analysis was conducted by analyzing articles, journals, and books relevant to the research problem. The findings show that in historical records there are figures who are considered "heroes"—those with courage and support—or "traitors" by society for their roles. In the G30S/PKI incident, the figures who became heroes were Soeharto and his military forces of Army officers, while the traitors were PKI members and supporting mass organizations. In the Situjuh incident, Kamaluddin was labeled a traitor for leaking information about the meeting location to the Dutch, which triggered the Situjuh incident. Then, in the historical events of the struggle for independence, there were figures who were considered heroes, namely Prince Diponegoro and Soekarno. However, the historical narrative still needs to be criticized because there are various different perspectives in examining the role of heroes and traitors of the figures involved. There are many factors that can influence the moral assessment and role of historical figures. Thus, a more in-depth and comprehensive identification is expected in historiographical studies. Keywords: Heroes, Historical Events, Individual Roles, Traitors